Effect of preceding crops on growth and yield of zero-till rabi castor (Ricinus communis L.) under different nitrogen levels: EFFECT OF PRECEDING CROPS ON GROWTH AND YIELD OF ZERO-TILL RABI CASTOR - M MADHU; M VENKATA RAMANA (Journal of Oilseeds Research, 2017)
An experiment was conducted to find out the effect of preceding crops on growth and yield of zero-till rabi castor under different nitrogen levels during kharif and rabi seasons of 2010-11 and 2011-12. The results revealed that among different preceding kharif crops, greengram and bajra were found to have positive influence on growth parameters like plant height, dry matter production, number of leaves, LAI and seed yield (means yield of 3006 and 2832 kg/ha greengram and bajra, respectively) of castor compared to that of other preceding crops (groundnut and maize). Among nitrogen levels, with increase in nitrogen dose, there was significant increase in seed yield upto 120 kg N/ha (3221 kg/ha).